The Effectiveness of Reward-Based Strategies on the Responsible Behavior of Children Aged 4-5 Years - Al Fa'izza Fatirahma; Adriani Rahma Pudyaningtyas (Kumara Cendekia, 2026)
Responsibility is an important aspect of social-emotional development that should be introduced to children from an early age. Responsible behavior itself enables children to complete their tasks effectively, control themselves, and build harmonious relationships with their environment, thereby increasing their acceptance and likability by others. The impact on children who do not have responsible behavior is that they always depend on others and do not trust. Additionally, children often struggle to understand the norms and rules that exist in their environment. The purpose of this study was to determine the effectiveness of rewarding responsible behavior in early childhood children, especially those aged 4-5 years. This type of research employs quantitative methods with a quasi-experimental design, utilizing a one-group pretest-posttest approach. Data collection was conducted using observational techniques and a behavioral checklist. Based on the research data, the average pre-test value was 11.73, and then increased to 17.27 during the post-test. It can be concluded that giving rewards has an effect on the responsible behavior of children aged 4-5 years.